Implementation of Government Programs in Facilitating Employment Opportunities for Persons with Disabilities in Special Region of Yogyakarta - Putri Ramadhani; Suswanta Suswanta (Journal of Governance and Public Policy, 2019)
The level of welfare of persons with disabilities is still relatively low. This is partly due to limited access to employment opportunities. Special Region of Yogyakarta through Regional Regulation Number 4 of 2012 has made serious efforts to protect and fulfill the rights of persons with disabilities, particularly in the field of work. However, the employment of persons with disabilities in the formal sector is still low. Evidently, the results of monitoring the Special Region of Yogyakarta’s Manpower and Transmigration Office in 2016, only 24 of 325 companies that have employed persons with disabilities. Therefore, this study aims to examine the Yogyakarta Special Region government program in facilitating employment opportunities for persons with disabilities. Special Region of Yogyakarta’s Social Service through the activities of the Mobile Social Services Unit; providing motivation and strengthening social mentality; skills guidance; Training in Loka Bina Karya; Job Learning Practices; and some capital activities have been carried out to prepare workers with disabilities. However, skills training is considered to be traditional in nature and only trains basic-level abilities. Thus, the competencies of persons with disabilities do not match the qualifications required by the company. In addition, the unavailability of accessibility is also the reason companies have not employed workers with disabilities. Furthermore, the Department of Manpower and Transmigration Special Region of Yogyakarta conducts disability-friendly labor market activities in collaboration with non-governmental organizations to increase employment opportunities for persons with disabilities. Promoting and giving rewards to companies is also carried out to encourage the absorption of workers with disabilities in the formal sector. However, there are still many companies/agencies that have not employed persons with disabilities in accordance with the mandate of Law Number 8 of 2016.